Search for R-parity violating decays of a top squark in proton-proton collisions at $\sqrt{s}$ = 8 TeV - CMS collaboration (2284 authors) (2016)
The results of a search for a supersymmetric partner of the top quark (top squark), pair-produced in proton–proton collisions at s=8 TeV , are presented. The search, which focuses on R-parity violating, chargino-mediated decays of the top squark, is performed in final states with low missing transverse momentum, two oppositely charged electrons or muons, and at least five jets. The analysis uses a data sample corresponding to an integrated luminosity of 19.7 fb −1 collected with the CMS detector at the LHC in 2012. The data are found to be in agreement with the standard model expectation, and upper limits are placed on the top squark pair production cross section at 95% confidence level. Assuming a 100% branching fraction for the top squark decay chain, t˜→tχ˜1±,χ˜1±→ℓ±+jj , top squark masses less than 890 (1000) GeV for the electron (muon) channel are excluded for the first time in models with a single nonzero R-parity violating coupling λijk′ (i,j,k≤2) , where i,j,k correspond to the three generations.